A Heuristic Method for Identifying Scam Ads on Craigslist - Alsaleh, Hamad; Zhou, Lina (2018 European Intelligence and Security Informatics Conference (EISIC), 2018)
Craigslist is a popular online customer-to-customer marketplace, which has attracted millions of consumers for trading and purchasing secondhand items. Because of the high financial return that sellers could gain from using this site and the anonymity option that the website provides to its users, Craigslist is highly subject to fraudulent activities. The primary objective of this study is to detect scam ads on Craigslist. Based on the related literature and our observations of ads collected from the platform, we develop a heuristic method for identifying scam ads. We evaluate the proposed heuristics by conducting an experiment and performing additional data analyses using real data. The results provide preliminary evidence for efficacy of the heuristics developed in this study.